2010
DOI: 10.1007/s00221-010-2329-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses of mirror neurons in area F5 to hand and tool grasping observation

Abstract: Mirror neurons are a distinct class of neurons that discharge both during the execution of a motor act and during observation of the same or similar motor act performed by another individual. However, the extent to which mirror neurons coding a motor act with a specific goal (e.g., grasping) might also respond to the observation of a motor act having the same goal, but achieved with artificial effectors, is not yet established. In the present study, we addressed this issue by recording mirror neurons from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 23 publications
6
75
0
3
Order By: Relevance
“…Do they also have an understanding of the action made with the tool? Clearly, when monkeys are exposed to the observation of an action which they master because of a prolonged sensorimotor training, mirror neurons in their premotor cortex fire during observation of actions performed with the tool [50]. More interestingly, after prolonged visual exposure to an action performed by an experimenter using a tool, some premotor mirror neurons have been shown to respond specifically to the observation of tool actions [47].…”
Section: Discussion (A) Individual Learning and Understanding Of The mentioning
confidence: 99%
“…Do they also have an understanding of the action made with the tool? Clearly, when monkeys are exposed to the observation of an action which they master because of a prolonged sensorimotor training, mirror neurons in their premotor cortex fire during observation of actions performed with the tool [50]. More interestingly, after prolonged visual exposure to an action performed by an experimenter using a tool, some premotor mirror neurons have been shown to respond specifically to the observation of tool actions [47].…”
Section: Discussion (A) Individual Learning and Understanding Of The mentioning
confidence: 99%
“…In fact, these works showed that while the observation of a human grasping induced neural firing, in contrast the grasping performed with a mechanical tool (a pair of pliers) did not induce the same activation. However, recent findings [35,36] demonstrated that after prolonged training with a tool also tool-object interactions become effective in triggering F5 response. Therefore, the presence of a mechanical device is not sufficient per se to eliminate motor resonance.…”
Section: Motor Resonance In Hrimentioning
confidence: 99%
“…Singleneuron recording studies in nonhuman primates have indicated that the parieto-frontal MNs discharge when one performs a specific action and when one observes another individual performing the same action (Bonini et al, 2010;Fogassi et al, 2005). A previous study indicated that the majority of grasping MNs in area F5 discharged irrespective of whether grasping was achieved using the right or the left hand, or a precision, whole-hand, or even oral grip (Rochat et al, 2010;Umiltà et al, 2008). Using Bnormal pliers^(i.e., opening and then closing the fingers to grasp) and Breverse pliers( i.e., closing and then opening the fingers to grasp), Umiltà et al (2008) showed that MNs discharged according to the motor goal (i.e., the meaning, to grasp), regardless of the type of pliers.…”
mentioning
confidence: 99%